Proceedings of the 2nd International Conference on Education Science and Social Development (ESSD 2019) 2019
DOI: 10.2991/essd-19.2019.80
|View full text |Cite
|
Sign up to set email alerts
|

Dealing with Students’ Aversion in Global Virtual Teams: Evidence from Czech Republic and Estonia

Abstract: The paper tackles with theories of virtual international teams and students' different perceptions on collaborating internationally in global virtual teams (GVT) based-projects. The study sheds light on managing virtual teams that involve students from some universities around the Baltic Sea and students studying at Tallinn and Helsinki branch of the Estonian Business School. It contributes to understanding how universities and schools deal with student unwillingness and co-operation barriers, when it comes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…These employers sought staff who were/had/could: 2010) also acknowledge that many students feel burdened and disadvantaged by nonproductive peers, resulting in poorer academic outcomes. Velinov et al (2019) noted that many students had an aversion to online team assignments, given that most assignments were team-based. They found that students' aversion to teamwork varied depending on their level of autonomy, based on whether working in a team was mandatory or optional.…”
Section: Employability Skillsmentioning
confidence: 99%
“…These employers sought staff who were/had/could: 2010) also acknowledge that many students feel burdened and disadvantaged by nonproductive peers, resulting in poorer academic outcomes. Velinov et al (2019) noted that many students had an aversion to online team assignments, given that most assignments were team-based. They found that students' aversion to teamwork varied depending on their level of autonomy, based on whether working in a team was mandatory or optional.…”
Section: Employability Skillsmentioning
confidence: 99%
“…However, Shultz et al (2010) also acknowledge that many students feel burdened and disadvantaged by nonproductive peers, resulting in poorer academic outcomes. Velinov et al (2019) noted that many students had an aversion to online team assignments, given that most assignments were team-based. They found that students' aversion to teamwork varied depending on their level of autonomy, based on whether working in a team was mandatory or optional.…”
Section: Employability Skillsmentioning
confidence: 99%
“…Their findings revealed the need for the development of individuals’ abilities for working with peers on global virtual project teams. Similarly, Velinov et al ’s (2019) investigation of the students’ aversion to global virtual teams necessitates the need to explore different students' perceptions of virtual team projects for innovative activities.…”
Section: Introductionmentioning
confidence: 99%